Efektifitas Penyuluhan Metode Simulasi “Pemenuhan Kebutuhan Gizi Seimbang & Pemanfaatan Bahan Pangan Lokal” terhadap Pengetahuan, Sikap, dan Perilaku Kader di Desa Panduman – Kecamatan Jelbuk – Kabupaten Jember - Sultanah Zahariah; Tita Rudini Yassin (Jurnal Gizi Prima (Prime Nutrition Journal), 2020)
Chronic malnutrition in toddlers, especially those with stunted growth, is one of health problems in Indonesia. The stunting cases increased in 2016 compared to a year earlier. The prevalence of stunting in several regions in East Java are still high, especially in Jember. Stunting has an impact not only on the physical growth, but also on the cognitive development and is related to the economic productivity in the future. One of the efforts to encourage the general public to exercise a healthy behavior and to consume balanced nutrition is through health promotion services at Posyandu (unified health services). The component that plays an important role in this case is “kader” (fronts). This study aims to analyze the effectiveness of the simulation of "fulfillment of balanced nutritional needs & utilization of local food" on the knowledge, attitudes and behavior of kader in Panduman-Jelbuk-Jember. The number of samples in this study was 36 kader in Panduman - Jelbuk - Jember. The analysis method used was T-test for normal distribution data, Mann Whitney-U and Wilcoxon for the data that were not normally distributed. Statistical test on the knowledge aspects results in p value 0.126, on attitude 0.740 and on behavior 0.004. Thus, it is concluded that there are insignificant differences in the aspects of knowledge and attitudes between before and after the treatment whereas significant differences occur in the behavioral aspects. However, changes in behavioral aspects leaned exactly towards behavior deterioration, which may be due to a bias in this study.